MANAJEMEN STRATEGI RUMAH ANAK PRESTASI NGINDEN DALAM MENDUKUNG PENYANDANG DISABILITAS DI KOTA SURABAYA TAHUN 2023 - Shabirah Putri Azzahra; Vidya Imanuari Pertiwi (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
Surabaya is the second largest city in Indonesia with the largest population, this does not make the Surabaya City Government silent, but continues to make breakthroughs, including in fulfilling the rights of children with disabilities so that Surabaya City has managed to excel from other cities by being named a Primary Level Child Friendly City for five consecutive years. The Surabaya City Government inaugurated a house or place of learning for children with disabilities in Surabaya City called "Rumah Anak Prestasi" in September 2022 as a form of fulfillment of the rights stated in Law Number 8 of 2016. Rumah Anak Prestasi (RAP) is the hope of the Surabaya City government for children with disabilities to be able to hone and develop the talents they have and make themselves valuable, both producing work that can be sold, and being able to return to the community with confidence. The method used in this research is descriptive qualitative. The focus of this research is to see, describe, and know the Strategic Management of Rumah Anak Prestasi Nginden in Supporting Persons with Disabilities in Surabaya City based on the theory of Strategic Management from Fred R. David (2016) which has 3 focuses in looking at strategic management, namely strategy formulation, strategy implementation, and strategy evaluation. The data collection techniques used in this research are interviews with informants, direct observation in the field, and documentation. In its implementation, Rumah Anak Prestasi has a reliable structure for children to develop their creativity so that they are expected to be able to compete in the community. The services and coaching carried out are also in accordance with the vision and mission and the existing service edicts.The obstacle in providing guidance to children with disabilities is that the quantity of instructors is not comparable to the quantity of children with disabilities who study there.Evaluation needs to be done so that the number of instructors can be added and coaching activities become more effective